Analysis of Distributed Power Access on Distribution Network Fault Location and Voltage Quality. (October 2020) - Li, Bohan; Xu, Chang; Huang, Ping; Zheng, Fangqin; Jiang, Dan; Wang, Jing
Abstract: Distributed Generation (DG) has a certain impact on distribution network fault location and voltage quality during the access process, which is worth studying. In this paper, the impact of distributed power on the two is discussed separately, and further technical analysis is carried out with an example.